How do you solve y=x-4 and y=2x using substitution?

3 Answers
May 1, 2018

x = -4
y = -8

Explanation:

We know that y = x - 4. We also know that y = 2x

This must mean that x - 4 = 2x. By 'substituting' y = 2x in the first equation, we have got a new equation in a single variable.
By solving,
-4 = 2x - x(subtracting x from both sides)
implies x = -4

Now we know that x = -4. y = 2x must mean that y = 2(-4)
implies y = -8

the value of x is -4 and y is -8

Explanation:

given equations are y=x-4 and y=2x
put y=2xin y=x-4 then we have 2x=x-4rArr2x-x=-4rArrx=-4 since y=2xrArry=-8

May 1, 2018

x=-4 and y=-8

Explanation:

Substitution means plugging one equation to another to solve for a variable, so:

Let's plug y=x-4 into y=2x

By plugging it in, you get x-4=2x

Move variables to one side and constants in another

x-2x=4

-x=4

x=-4

Since we found x, we can find y by plugging x back into either equations. Answer would be the same. To prove this, I'll plug x into both equations.

y=x-4=(-4)-4=-8

y=2x=2(-4)=-8

So, x=-4 and y=-8